2017
DOI: 10.15171/bi.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

pH responsive cross-linked polymeric matrices based on natural polymers: effect of process variables on swelling characterization and drug delivery properties

Abstract: Introduction: The current work was aimed to design and synthesize novel crosslinked pH-sensitive gelatin/pectin (Ge/Pec) hydrogels using different polymeric ratios and to explore the effect of polymers and degree of crosslinking on dynamic, equilibrium swelling and in vitro release behavior of the model drug (Mannitol). Methods: The Ge/Pec based hydrogels were prepared using glutaraldehyde as the crosslinker. Various structural parameters that affect their release behavior were determined, including swelling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 58 publications
1
12
0
1
Order By: Relevance
“…In this work, the pH value of the media was more than 4, which caused an increased swelling ratio, and as a result, faster degradation of the Ph-pectin hydrogel matrix due to the ionization of carboxyl groups and electrostatic repulsion of COO-. 42 Inconsistent with results obtained from the mechanical test, the mechanically weakest hydrogels degraded rapidly while the mechanically most robust hydrogels degraded later in both PBS and enzyme-containing solution. In Phpectin/Ph-gelatin, there are a higher number of Ph groups, which makes a larger number of crosslinking sites available.…”
Section: Biodegradationsupporting
confidence: 71%
See 1 more Smart Citation
“…In this work, the pH value of the media was more than 4, which caused an increased swelling ratio, and as a result, faster degradation of the Ph-pectin hydrogel matrix due to the ionization of carboxyl groups and electrostatic repulsion of COO-. 42 Inconsistent with results obtained from the mechanical test, the mechanically weakest hydrogels degraded rapidly while the mechanically most robust hydrogels degraded later in both PBS and enzyme-containing solution. In Phpectin/Ph-gelatin, there are a higher number of Ph groups, which makes a larger number of crosslinking sites available.…”
Section: Biodegradationsupporting
confidence: 71%
“…41 High cross-linked hydrogels are less acidic since amino groups are covered, which reduces the ionization process. 42 In tissue engineering, excess swelling should be avoided to prevent matrix disintegration. A useful method for diminishing the swelling is to create crosslinks which are not influenced under physiological situations.…”
Section: Swelling Ratiomentioning
confidence: 99%
“…The solvent interaction parameter χ was calculated by using the Flory-Huggins theory. 23,24 These parameters were used to determine whether the polymers were compatible with the molecules of the surrounding fluid. According to this theory, the following equation 5was used to determine χ:…”
Section: Determination Of Solvent Interaction Parameter ( χ )mentioning
confidence: 99%
“…It suggested that M C values were amplified by increasing the swelling ratios of Ge/SA gels. The following relation was used to determine M C : 24,25 (6)…”
Section: Molecular Weight Between the Crosslinksmentioning
confidence: 99%
“…Pectin is a hydrophilic polysaccharide present in the cell wall of most plants. Its structure is based on a linear chain of poly-α-(1→4)-dextro-galacturonic acid in which the carboxyl groups can be esterified by a variable number of methyl groups [37,38]. These carboxylic groups make pectin a pH-sensitive polymer with an acidic character [36].…”
Section: Introductionmentioning
confidence: 99%